ANALISIS TERHADAP LIMITASI WAKTU PENYIDIKAN OLEH KOMISI PEMBERANTASAN KORUPSI PADA KASUS BLBI - Sari, Aulia Hermastuti Turastananing; Zulfiani, Anita (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Along with advances in the economy and science and technology in society, world crime is also growing. One of them is crime in the form of criminal acts of corruption. This is coupled with law enforcement for members of conventional corruption crimes that have been proven to experience various obstacles. In 2019, there were changes to the Corruption Eradication Law, namely the authority given to the Corruption Eradication Committee (KPK) to carry out investigations. However, the authority to stop investigations at the Corruption Eradication Commission is considered to be contrary to the law enforcement policy of corruption as an extraordinary crime and reduces the independence of the Corruption Eradication Commission